In vitro effect of trees forages inclusion from the amazonian piedmont in supplements for cattle - Riascos Vallejos, A.R.; Rodríguez Hernández, R.; Quintero, Lina Y.; Vargas, Diana P. (Cuban Journal of Agricultural Science, 2024)
The in vitro effects of the inclusion of three native species and adapted to the Amazonian piedmont on supplements for cattle were evaluated. A total of seven treatments were constituted: T1) control (concentrate without trees), T2 and T3 (20 and 40 % of Trichantera gigantea inclusion, respectively), T4 and T5 (20 and 40 % of Piptocoma discolor inclusion, respectively), and T6 and T7 (20 and 40 % of Hibiscus rosa-sinensis inclusion, respectively). The in vitro technique of gas production was applied and the in vitro degradability of the dry matter and organic matter was determined. A completely randomized design with four repetitions per treatment was used. The higher gas production corresponded to the control (T1), although did not showed differences with respect to the treatment with 40 % Piptocoma (T5) (p=0.016). The lower values of accumulated gas production were obtained when including 20 % de Piptocoma (T4), which not differ of the treatments T2, T5, T6 and T7. The highest values of in vitro degradability of the dry matter corresponded to the control (T1) and the supplements with 20 % of Trichantera inclusion (T2) and 20 and 40 % of hibiscus (T6 and T7) (p<0.008). The lower degradability value was for T5. The highest figures of in vitro digestibility of organic matter corresponded to the control and to the supplement with 20 % of Ttrichantera (T2) and with hibiscus (T6 and T7) (p<0.0001). The rest of treatments had the fallowing performance: T4 > T3 > T5. It is concluded that the inclusion in the concentrate of 20 % of T. gigantea and 20 and 40 % of H. rosa-sinensis did not affected the DM and OM degradability of the supplement and improved the nutrition partition to higher deposition of the fermented matter as microbial biomass, when decreasing the gas production with respect to the concentrate without trees.